Landscape of secondary physical education teachers' professional development in South Korea. Issue 6 (24th July 2019) - Lee, Okseon; Choi, Euichang; Griffiths, Mark; Goodyear, Victoria; Armour, Kathleen; Son, Hyukjun; Jung, Hyunsoo
ABSTRACT: The purpose of this study was to examine the landscape of continuing professional development (CPD) for Korean secondary physical education (PE) teachers. Specifically, teachers' perceptions of the characteristics of CPD, factors determining the effectiveness of CPD, and outcomes of CPD were examined. Data were collected from online questionnaires ( n  = 251) and in-depth interviews with secondary PE teachers ( n  = 20). The quantitative data were analyzed using SPSS 20.0 and the qualitative data were subjected to content analysis using NVivo11. The findings revealed that Korean PE-CPD was characterized as (a) excessively institution-based, (b) distorting teachers' patterns of CPD participation depending on years of teaching experience, and (c) emphasizing sport skills development. The teachers described an effective PE-CPD program as having (a) novel, relevant, and practical content, (b) an active, interactive, and collaborative structure, and (c) a knowledgeable, open, and risk-taking program facilitator. CPD was perceived to have predominantly proximal outcomes, such as the acquisition and application of knowledge and skills for immediate use, indicating that the traditional format of CPD is limited in promoting teachers' continuous learning. The discussion addresses teachers' agentic actions through the processes of interpretation, decision-making and perception, framed by values and teacher education traditions within a Korean social context.